PENGARUH OVER EKSITASI PADA TRANSFORMATOR DISTRIBUSI DI GARDU INDUK SERPONG TERHADAP PENUAAN ISOLASI KERTAS DITINJAU DARI SISI TERMAL - Muhammad Luqmanul Hakim; Aris Kiswanto; M. Tony Prasetyo (MEDIA ELEKTRIKA, 2012)
Distribution of electricity to consumers through some process that begins from power plants to substations supplied (sub-station), then lowered into the substation -a low-voltage distribution substations. The distance is too far between the point on the voltage distribution in particular between the IBT to the parent distribution substation secondary voltage drop triggers, It is as well as on the distance between new or IBT IBT cilegon Gandul to trigger serpong substation secondary voltage drop at substation serpong.To stabilize the voltage of the secondary to the primary voltage on distribution transformer tap changer operation. Problems arise when the tap changer to operate too much will lead to the over-excitation of the distribution transformer. The side effects of the over-excitation also trigger an increase in temperature of the thermal transformer, so the effect on the components within it, is no exception to the isolation of paper inthe process of thermal temperature rise is accelerating aging insulating paper it self. The exixtence of aging insulating paper must be accompanied by the estimated number of clear that the replacement of aging insulating paper on time, so it requires the calculation of accurate data on the thermal temperature kenaiakan to aging transformer paper insulation.Keywords: electricity distribution process, reduced secondary voltage, over-excitation, aging insulating paper, the estimated value.